SPIRITUALITY IN THE PERSPECTIVE OF SACRED SCRIPTURES OF THE WORLD RELIGION - Razzaq, Tayyaba (PEOPLE: International Journal of Social Sciences, 2018)
Spirituality is a systemic practice and mostly experience of a religion. This is the most powerful, comprehensive and profound experience. The purpose of thisstudy is to investigate importance and the purpose of spirituality in world religion? And how much religious scriptures emphasized upon their followersto attain it? Most of the religious sacred texts have described thathuman being as a spiritual being.The physical domain needs personal hygiene too because it is pre-requisite for spirituality. Some purposeful physical activities of self-controlhelp to attain high level of spirituality. Our five senses and apparent bodyneed to be bounded by some set rules and religious laws. Spirituality can be achieved by some physical and mental training and control.This is the most prominent feature in world religion andeven persuaded to be practiced at particular sacred places. Methodology of this research study is descriptive. This research study has foundthat purpose of spirituality in world religion is to be closer to the Lord. Although the tools and methodologies to achieve spiritualityin world religions’ are different but the purpose is almost same as given in theirprescribed religious literature.